Improvement of medical care in a cohort of newborns with sickle‐cell disease in North Paris: impact of national guidelines. (7th April 2016) - Couque, Nathalie; Girard, Delphine; Ducrocq, Rolande; Boizeau, Priscilla; Haouari, Zinedine; Missud, Florence; Holvoet, Laurent; Ithier, Ghislaine; Belloy, Marie; Odièvre, Marie‐Héléne; Benemou, Michel; Benhaim, Patricia; et al.
Summary: We conducted a retrospective study on newborns with sickle‐cell disease (SCD), born 1995–2009, followed in a multicentre hospital‐based network. We assessed patient outcomes, medical care and compliance with the national guidelines published in December 2005. Data from 1033 patients (742 SS/Sβ°‐thalassaemia) with 6776 patient‐years of follow‐up were analysed (mean age 7·1 ± 3·9 years). SCD‐related deaths ( n  = 13) occurred only in SS‐genotype patients at a median age of 23·1 months, mainly due to acute anaemia ( n  = 5, including 2 acute splenic sequestrations) and infection ( n  = 3). Treatment non‐compliance was associated with a 10‐fold higher risk of SCD‐related death ( P  =   0·01). Therapeutic intensification was provided for all stroke patients ( n  = 12), almost all patients with abnormal transcranial Doppler (TCD) ( n  = 76) or with >1 acute chest syndrome/lifetime ( n  = 64) and/or ≥3 severe vaso‐occlusive crises/year ( n  = 100). Only 2/3 of patients with baseline haemoglobin <70 g/l received intensification, mainly for other severity criteria. Overall, hydroxycarbamide was under‐prescribed, given to 2/3 of severe vaso‐occlusive patients and 1/3 of severely anaemic patients. Nevertheless, introduction of the on‐line guidelines was concomitant with an improvement in medical care in the 2006–2009 cohort with a trend towards increased survival at 5 years, from 98·3% to 99·2%, significantly increased TCD coverage ( P  =   0·004) and earlier initiation of intensification of therapy ( P  ≤   0·01).